A study of influence of sugars on the modulations of dental plaque pH in children with rampant caries, moderate caries and no caries - Utreja D; Tewari A; Chawla H (Wolters Kluwer Medknow Publications, 2010)
The present study is undertaken to find out the pH of resting plaque in children with no caries, moderate caries and rampant caries and to determine the modulations of plaque pH with different sugar solution rinses viz: sucrose, glucose and fructose. The study was carried out on forty five children, in the age group of 3-10 years (25 males and 20 females). The child was given 10 ml of test solution and was asked to rinse and swish it in the mouth for a period of 30 sec. Plaque samples were taken from 20 different spots after 5, 10, 20 and 30 min of the rinse and pH values of all the samples were determined. Results show that there was a statistically significant (P<0.05) difference between the pH values of plaque at different intervals of time with sucrose, fructose and glucose solution rinse in children with moderate caries, rampant caries as compared to the caries free group. Sucrose was found to be highly cariogenic in all the children with a greater potentiating effect in moderate and rampant caries. Glucose also appeared to have a cariogenic role while fructose had the least of it all.